2002
DOI: 10.1126/science.1071065
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of T Cell-Dendritic Cell Interactions in Lymph Nodes

Abstract: T cell immune responses begin within organized lymphoid tissues. The pace, topology, and outcomes of the cellular interactions that underlie these responses have, so far, been inferred from static imaging of sectioned tissue or from studies of cultured cells. Here we report dynamic visualization of antigen-specific T cells interacting with dendritic cells within intact explanted lymph nodes. We observed immunological synapse formation and prolonged interactions between these two cell types, followed by the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
532
3
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(564 citation statements)
references
References 28 publications
23
532
3
6
Order By: Relevance
“…The absence of this specialized matrix in the iris stroma likely contributes to the slower speed that we observed for T cells migrating in the iris. Estimates of the average lateral speed of T cells in lymph node vary from 4 µm/min during an activation phase to about 11 µm/min in the absence of an antigenic challenge [4,6,33]. These are considerably faster than the 1-2 µm/min lateral speed reported here and likely reflect tissue-specific differences in the nature of chemotactic signals and/or the extracellular matrix along which the cells must navigate.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The absence of this specialized matrix in the iris stroma likely contributes to the slower speed that we observed for T cells migrating in the iris. Estimates of the average lateral speed of T cells in lymph node vary from 4 µm/min during an activation phase to about 11 µm/min in the absence of an antigenic challenge [4,6,33]. These are considerably faster than the 1-2 µm/min lateral speed reported here and likely reflect tissue-specific differences in the nature of chemotactic signals and/or the extracellular matrix along which the cells must navigate.…”
Section: Discussionmentioning
confidence: 52%
“…More recently in vivo documentation of T cell and APC trafficking and interactions have been documented, especially through the use of two photon confocal microscopy [4,5,6,7,8,9]. The majority of these studies involve the lymph node or other lymphoid organ such as the bone marrow or thymus [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…LPS, bacterial CpG DNA and double-stranded viral DNA) and large amounts of antigen. As a consequence, maturing DC rapidly up-regulate chemokine receptors, which favor their migration to the draining lymph nodes at a time at which IL-12 is maximally produced [56]. Here, early activated DC should rapidly induce CD4 + T cell activation [57], possibly Th1 polarization [46], and even faster priming of potent CTL [58,59] with Tc1 phenotype [29].…”
Section: Discussionmentioning
confidence: 99%
“…And he suggested that the random movement has a purpose, by helping a T cell range across a broad territory and find the 'antigen-presenting cell' carrying the precise antigen it recognizes. In 2002, the work was published in Science 2 as part of a trio of advanced microscopy papers exploring the dynamics of T cells 3,4 .…”
Section: Special Effectsmentioning
confidence: 99%